Priredbe literarnih del za mladino - Mohor, Miha (Revija za elementarno izobraževanje, 2013)
Adaptations of Literary Works for the Youth. It is commonly argued that adaptation impoverishes literary classics through a process of simplification, which updates them for specific reading public. The reason is that language and literature are inseparable and there is a rather complex relationship between the two. Yet the paper points out that since mid-19th century, the world classics have more often than not been retold for the first time in the shortened form. The simplified versions have not been made only to address Slovenian less-skilled readers or to approach juvenile reading abilities, but have been subjected to censorship for moral, religious, or ideological reasons. Because of a specific cultural context, Slovenian literary classics have been rarely shortened or adapted..
Keywords: classics; children literature; reception; adaptations; renditions